The Mediating Role of Entrepreneurial Resilience in Transforming Environmental Factor Turbulence into Sustainable Competitive Advantage - Hidayatinnisa’, Nurul; Setiawati, Riska Ayu; Nurfauziah, Suci (Jurnal Manajemen dan Inovasi (MANOVA), 2025)
Objective – This study aims to investigate the influence of Environmental Factor Turbulence (EFT) on Sustainable Competitive Advantage (SCA), with Entrepreneurial Resilience (ER) as a mediating factor, in the context of Micro, Small, and Medium Enterprises (MSMEs) in Malang. Design/methodology/approach – This research employs a quantitative approach using a survey method. Data were gathered from 150 MSME owners in Malang through structured questionnaires, and Structural Equation Modeling (SEM) PLS was utilized for analysis. The variables examined include Environmental Factor Turbulence, Entrepreneurial Resilience, and Sustainable Competitive Advantage. Findings – The results indicate that while Environmental Factor Turbulence does not directly influence Sustainable Competitive Advantage, its impact is significant when mediated by Entrepreneurial Resilience. Entrepreneurial Resilience plays a crucial role in enhancing the adaptability and strategic agility of MSMEs, enabling them to transform turbulence into opportunities for long-term competitiveness. Research limitations/implications – This study focuses on MSMEs in Malang, limiting its generalizability to other regions or sectors. Future research could explore similar frameworks in different geographical and sectoral contexts or employ longitudinal methods to assess resilience over time. Practical implications – The findings underscore the importance of fostering Entrepreneurial Resilience as a strategic priority for MSMEs. Policymakers and practitioners should implement capacity-building programs, provide financial support, and promote collaborative ecosystems to bolster resilience and ensure sustainable competitive advantage in dynamic environments.